Tracking self-assembly morphology of cationic peptide analogues using turbidimetric- potentiometric titration - Ling Tan, Huey; Pei Lim, Ying; Sufian Soâ€™aib, Mohomad (International Journal of Engineering and Technology, 2018)
Peptide amphiphiles are promising molecular materials for drug delivery systems and regenerative medicine through formation of well-ordered nanostructures. Rationally designed self-associating synthetic peptide analogues containing arginine (FEFEFRFR) and lysine (FEFEFKFK) were studied to understand the effect of pH and side chain interactions and its influence on the resulting nanostructure formation. Changes in structural conformation in bulk were followed by turbidimetric-potentiometric titrations with pH ranges from 4 to 11 and 4 to 12.6 for FEFEFKFK and FEFEFRFR respectively. Fourier Transform Infrared Spectroscopy (FTIR) was used to determine the secondary structure of the peptides while Field Emission Scanning Electron Microscopy (FE-SEM) was employed to study the morphology and dimension of higher order structures at various pH. Turbidity results showed that both FEFEFKFK and FEFEFRFR displayed higher turbidity level when their side chains were neutralized, in which FEFEFRFR showed higher turbidity level when arginine was neutralized. Both peptides exhibited similar self-assembly behavior in solution which mainly adopted antiparallel Î²-sheets conformation with spherical structures of different micro-metre size when there is a net charge of +2 or -2. FEFEFKFK was also found to form concaved disks and beads-on-a-string arrangement at pH 4. Both the peptide analogues were capable of forming smaller aggregates in a network of spherical structure at nanoscale when the net charge was near zero. This study ultimately provides a better understanding of predicting morphology and size of surface functional modification of self-assembled polypeptides.Â Â